Serum C-peptide level and the risk of cardiovascular diseases mortality and all-cause mortality: a meta-analysis and systematic review - Ahmadirad, Hamid; Teymoori, Farshad; Mokhtari, Ebrahim; Jahromi, Mitra Kazemi; Norouzzadeh, Mostafa; Tavakkoli, Saeed; Shahrokhtabar, Tahere; Farhadnejad, Hossein; Mirmiran, Parvin (Frontiers in Cardiovascular Medicine, 2023)
Aims and background Recently, the serum of C-peptide has been the focus of researchers as a possible predictor of mortality. However, the possible association of serum C-peptide with cardiovascular diseases (CVDs) mortality and all-cause mortality has not been clearly identified. This meta-analysis aimed to assess the relationship between serum C-peptide and the risk of CVDs mortality and all-cause mortality. Methods A comprehensive and systematic search was performed in various important databases, including the PubMed, Web of Science, and Scopus to find relevant studies up to November 2022. The reported hazard ratio (HR) [95% confidence interval (CI)] for all studies was converted into log HR, and their SD was calculated. Then to compute the pooled HR, the random-effects model with inverse variance weighting method was performed. Results Twenty-three studies were included in the meta-analysis. Fourteen studies reported HR for all-cause mortality, and nine studies for CVDs-related mortality. The pooled results indicate a significant association between serum C-peptide and the risk of all-cause mortality (HR: 1.22; 95% CI: 1.12–1.32, I2 = 76.8%; P-value < 0.001). Also, higher serum C-peptide was related to the increased risk of CVDs mortality (HR: 1.38; 95% CI: 1.08–1.77, I2 = 81.8%; P-value = 0.012). Conclusions Our investigation suggested that an increased level of serum C-peptide is associated with a higher risk of both CVDs and all-cause mortality. Further, large-scale studies and sufficient samples are recommended to present a convincing link between C-peptide and the risk of CVDs and all-cause mortality. Systematic Review Registration identifier, CRD42022364842.